Upaya Peran Guru PAI untuk Meningkatkan Kemampuan Berpikir Kritis Siswa melalui Pembelajaran Berbasis Masalah pada Mata Pelajaran Pendidikan Agama Islam - Rosalinda Rosalinda; Selly Pitia; Syukri Syukri; Kurniati Kurniati (JURNAL ILMIAH NUSANTARA, 2025)
Islamic Education (PAI) plays a crucial role in character building, particularly in enhancing critical thinking skills through Problem-Based Learning (PBL). This study aims to explore the efforts of PAI teachers in implementing PBL to encourage active student participation in the learning process. Using a qualitative approach, this research analyzes literature and documents related to PBL and critical thinking. The results indicate that PBL not only improves students' understanding of religious teachings but also hones their analytical and problem-solving skills. Teachers act as facilitators who create a challenging learning environment, encouraging students to explore relevant moral and social issues. Through group discussions and reflections, students learn to appreciate diverse perspectives and develop critical thinking abilities. This study concludes that PBL is effective in enhancing the critical thinking skills of PAI students, and it is recommended that teachers continue to develop competencies in applying this method to create more relevant and participatory learning experiences.